Factors Influencing Environmental Conservation Behavior of Employees in an Electronic Component Manufacturing Company - Tanatrinchat, Kornkanok; Akkawanitcha, Chuanchuen (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
This research aimed to study (1) level of problem awareness, awareness of consequences, ascription of responsibility, personal norm pro-environmental behavior, and pro-environmental behavior; (2) influence of problem awareness, awareness of consequences, ascription of responsibility to personal norm pro-environmental behavior; and (3) influence of personal norm pro-environmental behavior to pro-environmental behavior. The research collected information from 300 employees of an electronic component manufacturing company in Ratchaburi Province, by the quota sampling method. The research tool was a questionnaire. analysis of data by frequency, percentage, mean, standard deviation, Pearson’s product-moment correlation and regression analysis. The research results were found as follows: most of the respondents were female, aged less than or equal to 30 years old, with undergraduate education, and a monthly income of less than or equal to 15,000 baht. The results of the data analysis at the opinion level revealed that opinion of variables by problem awareness, awareness of consequences at a high level, then opinion of variables by ascription of responsibility, personal norm pro-environmental behavior, and pro-environmental behavior at the highest level. The hypothesis testing results showed that problem awareness and ascription of responsibility positively influence personal norm pro-environmental behavior and personal norm pro-environmental behavior positively influence pro-environmental behavior statistically significant at level 0.05. While awareness of consequences has a negative influence on personal norms, the statistically insignificant. The findings from this research can be applied to relevant organizations as well to enable personnel in the organization to have more environmental conservation behaviors.